2023
DOI: 10.3390/jcm12082815
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Outcomes in Flexible Ureteroscopy: A Narrative Review of Suction Techniques

Abstract: Objective: The aim of this review is to summarize the existing suction systems in flexible ureteroscopy (fURS) and to evaluate their effectiveness and safety. Methods: A narrative review was performed using the Pubmed and Web of Science Core Collection (WoSCC) databases. Additionally, we conducted a search on the Twitter platform . Studies including suctions systems in fURS were included. Editorials, letters and studies reporting intervention with semirigid ureteroscopy, PCNL and mPCNL were excluded. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Among the suction modalities, the use of UAS with suction exhibited lower complication rates, shorter operative times, and reduced incidences of postoperative fever and SIRS. They can control intrarenal pressure, thereby improving visualization and stone fragment removal without the requirement for retrieval baskets ( 51 ).…”
Section: Methodsmentioning
confidence: 99%
“…Among the suction modalities, the use of UAS with suction exhibited lower complication rates, shorter operative times, and reduced incidences of postoperative fever and SIRS. They can control intrarenal pressure, thereby improving visualization and stone fragment removal without the requirement for retrieval baskets ( 51 ).…”
Section: Methodsmentioning
confidence: 99%
“…All of the above factors make suction incorporated small calibre UAS, the need of the hour. Suction techniques in RIRS can be of 3 types -Irrigation/suctioning system with control of pressure, direct in scope suction (DISS) and suction ureteral access sheath (sUAS) [11]. It is shown that suction incorporation improves the stone free rates and reduces the complication rates [11].…”
Section: Introductionmentioning
confidence: 99%
“…Suction techniques in RIRS can be of 3 types -Irrigation/suctioning system with control of pressure, direct in scope suction (DISS) and suction ureteral access sheath (sUAS) [11]. It is shown that suction incorporation improves the stone free rates and reduces the complication rates [11]. On comparing the results of RIRS done using DISS with those of sUAS, Gauhar et al found that, 33.3% of patients in DISS group required a further RIRS whereas only 3.6% of sUAS group required further intervention [12].…”
Section: Introductionmentioning
confidence: 99%